The SPECTRAL perfusion arm clamping dAtaset (SPECTRALPACA) for video-rate functional imaging of the skin - Ayala, Leonardo; Mindroc-Filimon, Diana; Rees, Maike; Hübner, Marco; Sellner, Jan; Seidlitz, Silvia; Tizabi, Minu; Wirkert, Sebastian; Seitel, Alexander; Maier-Hein, Lena (Scientific data, 2024)
Spectral imaging has the potential to become a key technique in interventional medicine as it unveils much richer optical information compared to conventional RBG (red, green, and blue)-based imaging. Thus allowing for high-resolution functional tissue analysis in real time. Its higher information density particularly shows promise for the development of powerful perfusion monitoring methods for clinical use. However, even though in vivo validation of such methods is crucial for their clinical translation, the biomedical field suffers from a lack of publicly available datasets for this purpose. Closing this gap, we generated the SPECTRAL Perfusion Arm Clamping dAtaset (SPECTRALPACA). It comprises ten spectral videos (∼20 Hz, approx. 20,000 frames each) systematically recorded of the hands of ten healthy human participants in different functional states. We paired each spectral video with concisely tracked regions of interest, and corresponding diffuse reflectance measurements recorded with a spectrometer. Providing the first openly accessible in human spectral video dataset for perfusion monitoring, our work facilitates the development and validation of new functional imaging methods.
Online veröffentlicht: 25. Mai 2024
Gesehen am 08.01.2025